You are loveable: an anthology of dating stories - Bijjala, Sudheeshna (Nanyang Technological University, 2024)
In this contemporary age of dating, there is no longer a ‘normal’ way of meeting someone; from apps to arranged marriages and night clubs to BTOs, the realities of dating in Singapore have never been so frustratingly convoluted and diverse. Informed by interviews of Singaporean youth and their real dating experiences, You Are Loveable seeks to showcase the lesser-known yet common dating stories happening right under your noses. By doing so, it hopes to show that no matter your dating struggles, silly or severe, you will always be loveable.